Participação feminina na política: análise das eleições gerais de 2018 e 2022 para o legislativo federal de Mato Grosso do Sul - Amanda Ortiz Pompeu (2025)
The research problem seeks to understand how female participation in politics in the state of Mato Grosso do Sul is characterized in the 2018 and 2022 general elections for the federal legislature, considering the factors that influence women's candidacy, election, and representation in this context. The main objective is to evaluate female participation in politics in the state of Mato Grosso do Sul, focusing on the analysis of the 2018 and 2022 federal legislative elections. To this end, the research will discuss the evolution of women's political rights in Brazil, before and after the 1988 Federal Constitution. The models of gender electoral quotas and their effectiveness in the electoral scenario will be examined, addressing the types of electoral fraud that occurred in women's campaigns. The research also analyzed the profile of women candidates and women effectively elected, evaluating the existing characteristics and their impacts on the process of gender equality. Finally, the research will explore the challenges that politics in Mato Grosso do Sul faces in ensuring the inclusion of women in politics, reflecting on the strategies that can be adopted to achieve Sustainable Development Goal 5, especially target 5.5, of the 2030 Agenda. The study uses the hypothetical-deductive method, with a focus on exploratory, qualitative and descriptive research, based on the analysis of electoral data and statistics, relevant legislation, academic publications and scientific articles aimed at understanding the topic. Thus, this study highlighted the difficulties faced by women before and during electoral campaigns, including low financial support and the lack of advice from political parties to women.